Harnessing enzyme promiscuity of alditol-2-dehydrogenases for oxidation of alditols to enantiopure ketoses - Prithwiraj De; Jenna Salvat; Eliza Walthers; James Henriksen; Michael Wells; Richard T. Conant; Claudia M. Boot (PLoS ONE, 2025)
Several alditol-2-dehydrogenase enzymes from the short chain dehydrogenase (SDR) family catalyze the production of enantiopure rare ketoses from alditols as substrates and are used in biotech industry. Clearly, the absolute configuration of the internal chiral carbons in the open-chain conformation of alditols provides the structural basis for the enzymatic operation. This also allows for substrate ambiguity that manifest as enzyme promiscuity due to partial stereoselectivity of the enzyme. The issue is to make the right choice of a promiscuous enzyme and access maximum product diversity. Based on the absolute configuration of a cohort of ten enantiopure hexitols, this study is a systematic exploration of the stereochemical foundation of enzyme promiscuity in alditol-2-dehydrogenases which does not involve any kinetic analysis. Using cell-free expressed galactitol-2-dehydrogenase (G2DH), D-sorbitol-2-dehydrogenase (D-S2DH), and D-altritol-5-dehydrogenase (D-A5DH), we confirmed chemoenzymatic synthesis of all enantiopure ketohexoses through characterization by GC/MS and NMR spectroscopy. However, we found that enzyme promiscuity is beyond the partial stereoselectivity for certain alditol-2-dehydrogenase enzymes that are reliably producing enantiopure ketoses from multiple alditols. For instance, G2DH oxidizes galactitol (2R 3S; 55% conversion), a meso-alditol with a plane of symmetry, as well as L-talitol (2S 3S; 2.1% conversion) to L-tagatose. The substrate bears different absolute/relative configurations and is an example among several promiscuous oxidations. Notably, their product yields are different under similar reaction conditions indicating stereochemical preference of the enzyme. This in vitro chemoenzymatic investigation of the underlying stereochemical interplay for the enantioselective oxidation of alditols explores the potential to harness enzyme promiscuity/substrate-adaptability as a tool for the predictive synthesis of multiple enantiopure ketoses. This study focuses on unconventional stereochemical investigation into enzyme stereospecificity and promiscuity which precludes kinetic analysis. Given the role of enzyme promiscuity in evolutionary processes, systematic stereochemical analysis may prove crucial in future.